Anatomy, magnetic resonance and arthroscopy of the popliteal hiatus of the knee: normal aspect and pathological conditions. Issue 1 (January 2021) - Grassi, Alberto; Pizza, Nicola; Andrea Lucidi, Gian; Macchiarola, Luca; Mosca, Massimiliano; Zaffagnini, Stefano
Abstract : The popliteal hiatus is a complex region, formed by the confluence of various structures connecting the meniscus, popliteal tendon, tibia and fibula. The main structures that can be found are the three popliteomeniscal fascicles (anterior, postero-inferior and postero-superior), the lateral and posterior meniscotibial ligaments, the popliteofibular ligament and the meniscofibular fascicle. These structures can be identified in most cases using magnetic resonance imaging, and their 'static' assessment can be performed. Arthroscopic assessment is useful in identifying and testing 'dynamically' the integrity of the structures around the popliteal hiatus. Injuries or abnormalities of the popliteal hiatus and its structures could result in meniscal hypermobility and subluxation; however, these injuries are often unrecognized. Possible abnormalities in this region, apart from the well-known bucket-handle meniscal tear, are the Wrisberg Type III discoid meniscus, and meniscal fascicles tears. Cite this article: EFORT Open Rev 2021;6:941-954. DOI: 10.1302/2058-5241.6.200089